Pendugaan Populasi Penyu Hijau (Chelonia Mydas) di Pulau Jemur Kabupaten Rokan Hilir Riau - Bidasari bidasari; Retna Astuti Kuswardani; Jamilah Nasution (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
Research on the estimation of green turtle population (Chelonia mydas) was conducted in Jemur Island of Rokan Hilir Regency of Riau Province in May-June 2012. The purpose of this research is to estimate the green turtle population in Jemur Island Rokan Hilir regency, Riau Province. The research method used is the absolute method of absolute sampling that results in the number of population estimates in the form of the number of individuals per unit of sand surface units or habitats observed. The results showed that the number of different individuals as many as 229 nests. The condition of Jemur Island indicates the suitability of location for green turtle habitat to lay and incubate eggs. Physical factors corresponding to the distribution of saraang are said to be productive, ie the average number of nests per day of 8 (eight) nests or 8 (eight) different individuals. Of the 229 nests observed, the depth of the hive ranged from 60cm - 80cm and did not significantly affect the number of eggs placed with the results of correlation (r = 0.43).